2021
DOI: 10.7759/cureus.13086
|View full text |Cite
|
Sign up to set email alerts
|

Combined Diagnostic Accuracy of Total Leukocyte Count, Neutrophil Count, and Ultrasonography for the Diagnosis of Acute Appendicitis

Abstract: Acute appendicitis is a common surgical emergency that classically presents with right lower abdominal pain and tenderness on palpation. The diagnosis is often based on clinical examination in order to avoid the complications of surgery delay, yielding a high rate of negative appendectomies. Ultrasonography is a regularly used modality for establishing the diagnosis, whereas abdominal computed tomography (CT) is often used in sonologically equivocal cases. Other parameters include total leukocyte count, granul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The NEU count highlights the active and ongoing inflammatory state, while the LYM count highlights the regulatory pathway [15]. According to [16]. The AUC of NLR (0.81) was determined to be lower in our study than in the literature.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The NEU count highlights the active and ongoing inflammatory state, while the LYM count highlights the regulatory pathway [15]. According to [16]. The AUC of NLR (0.81) was determined to be lower in our study than in the literature.…”
Section: Discussionmentioning
confidence: 52%
“…According to Hajibandeh et al, NLR is a promising marker that can predict the diagnosis and severity of AA with a cutoff value of 4.7, AUC of 0.96, sensitivity of 88.89%, and specificity of 90.91% [ 4 ]. Fatima et al calculated the sensitivity of the NUE test as 88.03% and specificity as 92.86% in the diagnosis of AA (AUC 0.904) [ 16 ]. The AUC of NLR (0.81) was determined to be lower in our study than in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…WBC is commonly used for confirming any suspected inflammation or infection in the body. Fatima et al, in 2021, revealed that the accuracy of total leucocyte count > 11,000/mm 3 (as a diagnostic tool) was found to be 82.94%, with sensitivity and specificity being 83.10% and 82.14%, respectively [ 6 ]. A study conducted in India by Shafi et al in 2009 showed the sensitivity and specificity of WBC as 97.82% and 55.55%, respectively [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…These highly sophisticated markers are difficult to apply in clinical practice but the raise of neutrophil count in peripheral blood may be regarded as simplified method for monitoring of neutrophils activation. Although neutrophils activation can be measured by released cytokines, simple measurement of neutrophil counts derangements in peripheral blood count analysis was proposed as a sufficient marker of inflammation [ 103 , 104 , 105 ], easy to obtain and repetitive.…”
Section: Neutrophil To Lymphocyte Ratio (Nlr)mentioning
confidence: 99%